Pengaruh Motivasi Kerja dan Budaya Sekolah terhadap Kinerja Guru SMA di Kecamatan Purbolinggo - Nur Siwi Fitrianingrum; Sudirman Aminin; Riyanto Riyanto (Penerbit Goodwood, 2022)
Purpose: (1) The Impact of Work Inspiration on the Exhibition of Secondary Teachers in Purbolinggo Subdistrict, East Lampung Regime; (2) The Impact of School Culture on the Presentation of Secondary Teachers in Purbolinggo Subdistrict, East Lampung Rule; (3) The impact of Work Inspiration and School Culture together on the Presentation of Secondary Teachers in Purbolinggo Subdistrict, East Lampung Rule. Research methodology: Data analysis techniques used are (1) descriptive analysis; (2) prerequisite test of analysis includes normality test, linearity test and homogeneity test. Results: The result (1) there is a significant influence between work motivation on teacher performance; (2) school culture affects teacher performance based; and (3) there is an influence of Work Motivation and School Culture on teacher performance. Limitations: Data collection techniques on research background only with interviews. Contribution: The outcome can be use to assess the adequacy of the execution of schooling programs on working on the presentation.